(untitled) (International Journal of Studies in Nursing, 2020)
The benefits of postsecondary education (PSE) are well documented and yet historic challenges have contributed to significant underrepresentation of students with disabilities. This paper presents the results of a survey study that explored students with disabilities’ experiences of transfer between PSE institutions in Canada. Data was collected using a survey questionnaire developed by the research team. Rating questions were analyzed using descriptive data. Students also answered open-ended questions that were analyzed using a qualitative content analysis approach. Sixty-nine of the 248 survey responses received indicated involvement in transfer between PSE institutions, mostly college to university. Four out of 5 of the transfer students self-identified as having psychiatric and mental health disabilities (e.g., anxiety, depression). Perceptions and experiences among successful and non-successful transfer students were mixed. Fully one-third of transfer students indicated that they felt that college-university transfer may be a better route for PSE for students with disabilities than going straight to university. Barriers to college-university transfer, among others, included a lack of information about who can assist with the process (62.5%) and inadequate information about disabilities and accommodation (56.3%). The results of this snapshot of PSE students with disabilities’ perceptions of college-university transfer may inform the design of evidence-based PSE transition interventions for this population. Additionally, given the under-representation of Indigenous and other racialized students in PSE, there is merit in further investigation focusing on their transfer experiences.